Effects of integrating legumes or trees on soil C stock and organic matter dynamics in tropical grasslands - Souza de Sousa, Camila Eduarda (2024)
The utilization of integrated systems in livestock production has been implemented as a practice aimed at intensifying pasture area utilization while maintaining sustainable soil management to enhance total organic carbon (TOC) storage. However, the dynamics of organic carbon in the soil of integrated systems, involving the inclusion of legumes or tree components in pastures, are not fully understood. Our research assessed soils from pastures composed of grass-legume consortia (GLS), silvopastoral systems (SPS), and monoculture grass pastures (MP), comparing them to native forest soil (NF) in the Cerrado biome, at different evaluation depths: 0–5 cm, 5–10 cm, 10–20 cm, and 20–30 cm. The objective was to evaluate the potential of each system to store carbon in the soil in contrast to native forest soil by determining the labile carbon, water-soluble organic carbon, microbial biomass carbon, total carbon, total nitrogen, carbon management index, and soil carbon stock. No differences were observed for TOC and soil carbon stock between GLS and SPS, but both were demonstrated to be lesser than in the NF soil (p < 0.05). SPS, MP, and NF did not differ in terms of labile carbon, water-soluble carbon, and microbial biomass carbon content (p > 0.05), while GLS did not show similarity to NF in any of the analyzed variables (p < 0.05). Only the SPS achieved a CMI >100 in all soil depth ranges evaluated. Our study demonstrated that the association among labile carbon fractions dynamics and the relationship between CMI and soil biological attributes can be used as a proxy for TOC dynamics and indicators of a production system's potential to sequester carbon in the soil. Collectively, the studied variables indicate that the silvopastoral system exhibited greater potential for carbon recovery compared to the grass-legume integration system or monoculture grass pasture.